Randomised trial of fluid restriction in ventilated very low birthweight infants. Issue 2 (1st September 2000) - Kavvadia, V; Greenough, A; Dimitriou, G; Hooper, R
Abstract : BACKGROUND: Fluid restriction has been reported to improve survival of infants without chronic lung disease (CLD), but it remains unknown whether it reduces CLD in a population at high risk of CLD routinely exposed to antenatal steroids and postnatal surfactant without increasing other adverse outcomes. AIM: To investigate the impact of fluid restriction on the outcome of ventilated, very low birthweight infants. STUDY DESIGN: A randomised trial of two fluid input levels in the perinatal period was performed. A total of 168 ventilated infants (median gestational age 27 weeks (range 23–33)) were randomly assigned to receive standard volumes of fluid (60 ml/kg on day 1 progressing to 150 ml/kg on day 7) or be restricted to about 80% of standard input. RESULTS: Similar proportions of infants on the two regimens had CLD beyond 28 days (56% v 51%) and 36 weeks post conceptional age (26% v 25%), survived without oxygen dependency at 28 days (31% v 27%) and 36 weeks post conceptional age (58% v 52%), and developed acute renal failure. There were no statistically significant differences between other outcomes, except that fewer of the restricted group (19% v 43%) required postnatal steroids (p < 0.01). In the trial population overall, duration of oxygen dependency related significantly to the colloid (p < 0.01), but not crystalloid, input level; after adjustment for specified covariates, the hazard ratio was 1.07 (95% confidence interval 1.02 to 1.13). CONCLUSIONS: In ventilated, very low birthweight infants, fluid restriction in the perinatal period neither reduces CLD nor increases other adverse outcomes. Colloid infusion, however, is associated with increased duration of oxygen dependency.